Pengaruh Pengunaan Abu Ampas Kopi sebagai Bahan Subtitusi Semen pada Beton Pori - Saputra, Yusaq Bahyu; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
Pervious concrete is a material with open voids that allow water to flow through, making it highly effective in reducing surface runoff and increasing groundwater infiltration in urban areas. Pervious concrete, also known as porous concrete, is an innovative material designed with open pores that allow water to pass through its structure, making it a potential solution for mitigating surface runoff and enhancing groundwater infiltration in urban areas. This study focuses on the sustainable utilization of coffee waste by using coffee grounds ash as a cement substitute in environmentally friendly pervious concrete. In addition to producing environmentally friendly concrete, this study also provides an effective alternative for reducing organic waste. The study aims to analyze the effect of using coffee grounds ash as a partial cement replacement on the compressive strength of concrete, while simultaneously providing an innovative solution for the utilization of coffee waste by incorporating coffee grounds ash as a cement substitute in pervious concrete, specifically at cement replacement levels of 0%, 2,5%, 5%, and 7,5%. The concrete mix design was prepared according to the ACI 522R-10 method. Test results indicated that the 0% and 2,5% replacement levels produced a compressive strength of 5,91 MPa, while the 5% and 7,5% levels produced 4.43 MPa at 7 days, demonstrating that lower replacement levels provide higher compressive strength compared to higher replacement levels.